"What Time Is It?" - Hugh Hardy (Oz, 1990)
"What Time Is It?" considers a malaise I have about the relationship of preservation to contemporary architecture. Each of the projects presented here (with the exception of the last), was tailored for approval by the New York City Landmarks Preservation Commission.